Blocking P2Y2 purinergic receptor prevents the development of lipopolysaccharide-induced acute respiratory distress syndrome - Kargarpour, Zahra; Cicko, Sanja; Köhler, Thomas C.; Zech, Andreas; Stoshikj, Slagjana; Bal, Christina; Renner, Andreas; Idzko, Marco; El-Gazzar, Ahmed (Frontiers in Immunology, 2023)
Acute respiratory distress syndrome (ARDS) is associated with high morbidity and mortality resulting from a direct or indirect injury of the lung. It is characterized by a rapid alveolar injury, lung inflammation with neutrophil accumulation, elevated permeability of the microvascular-barrier leading to an aggregation of protein-rich fluid in the lungs, followed by impaired oxygenation in the arteries and eventual respiratory failure. Very recently, we have shown an involvement of the Gq-coupled P2Y2 purinergic receptor (P2RY2) in allergic airway inflammation (AAI). In the current study, we aimed to elucidate the contribution of the P2RY2 in lipopolysaccharide (LPS)-induced ARDS mouse model. We found that the expression of P2ry2 in neutrophils, macrophages and lung tissue from animals with LPS-induced ARDS was strongly upregulated at mRNA level. In addition, ATP-neutralization by apyrase in vivo markedly attenuated inflammation and blocking of P2RY2 by non-selective antagonist suramin partially decreased inflammation. This was indicated by a reduction in the number of neutrophils, concentration of proinflammatory cytokines in the BALF, microvascular plasma leakage and reduced features of inflammation in histological analysis of the lung. P2RY2 blocking has also attenuated polymorphonuclear neutrophil (PMN) migration into the interstitium of the lungs in ARDS mouse model. Consistently, treatment of P2ry2 deficient mice with LPS lead to an amelioration of the inflammatory response showed by reduced number of neutrophils and concentrations of proinflammatory cytokines. In attempts to identify the cell type specific role of P2RY2, a series of experiments with conditional P2ry2 knockout animals were performed. We observed that P2ry2 expression in neutrophils, but not in the airway epithelial cells or CD4+ cells, was associated with the inflammatory features caused by ARDS. Altogether, our findings imply for the first time that increased endogenous ATP concentration via activation of P2RY2 is related to the pathogenesis of LPS-induced lung inflammation and may represent a potential therapeutic target for the treatment of ARDS and predictably assess new treatments in ARDS.